European Biological Variation Study (EuBIVAS): within- and between-subject biological variation estimates for serum thyroid biomarkers based on weekly samplings from 91 healthy participants - Bottani, Michela; Aarsand, Aasne K.; Banfi, Giuseppe; Locatelli, Massimo; Coskun, Abdurrahman; Diaz-Garzon, Jorge; Fernandez-Calle, Pilar; Sandberg, Sverre; Ceriotti, Ferruccio; Carobene, Anna; Chem, European Federation Clinical (WALTER DE GRUYTER GMBH, 2022)
Objectives Thyroid biomarkers are fundamental for the diagnosis of thyroid disorders and for the monitoring and treatment of patients with these diseases. The knowledge of biological variation (BV) is important to define analytical performance specifications (APS) and reference change values (RCV). The aim of this study was to deliver BV estimates for thyroid stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3), thyroglobulin (TG), and calcitonin (CT). Methods Analyses were performed on serum samples obtained from the European Biological Variation Study population (91 healthy individuals from six European laboratories

21-69 years) on the Roche Cobas e801 at the San Raffaele Hospital (Milan, Italy). All samples from each individual were evaluated in duplicate within a single run. The BV estimates with 95\% CIs were obtained by CV-ANOVA, after analysis of variance homogeneity and outliers. Results The within-subject (CVI) BV estimates were for TSH 17.7\%, FT3 5.0\%, FT4 4.8\%, TG 10.3, and CT 13.0\%, all significantly lower than those reported in the literature. No significant differences were observed for BV estimates between men and women. Conclusions The availability of updated, in the case of CT not previously published, BV estimates for thyroid markers based on the large scale EuBIVAS study allows for refined APS and associated RCV applicable in the diagnosis and management of thyroid and related diseases.
Keywords: analytical performance specification; biological variation; reference change value; thyroid